The Function Of State Duty In Providing Legal Assurance On Online Buying Selling Agreements - Suwarno, Indra Gunawan; Haryanto, Imam (Universitas Pakuan, 2024)
The rapid development of digital technology has transformed the traditional trading system into a digital marketplace that relies on electronic transactions or e-commerce. As online buying and selling activities continue to expand, legal issues concerning the validity and enforceability of electronic agreements have emerged, particularly regarding the role of stamp duty as an instrument of legal assurance. This study aims to analyze the function of stamp duty in providing legal certainty for online sales and purchase agreements under Law Number 10 of 2020 on Stamp Duty and Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law). Employing a qualitative normative legal approach, this research examines statutory regulations, legal doctrines, and relevant literature to interpret the legal status of e-stamps in electronic contracts. The findings reveal that stamp duty serves dual functions—first, as a fiscal instrument for state revenue generation, and second, as a juridical basis for ensuring document authenticity and legal enforceability. The study concludes that the inclusion of a physical or electronic stamp duty (e-stamp) on digital contracts does not solely determine legality but strengthens evidentiary value and public trust in online transactions. The modernization of stamp duty regulation thus represents the government’s effort to adapt fiscal and legal systems to the digital economy, ensuring fairness, transparency, and legal certainty in e-commerce practices.